Entre santos e demônios: a percepção do mal na teologia e hagiografias do Reino Visigodo de Toledo (séculos VI-VII) - Esteves, Germano Miguel Favaro [UNESP] (2015)
This thesis about the Visigoth kingdom makes use of a genre of sources, the hagiography, as a starting point for the proposed approach. These sources show us an testimony of the imaginary in their imbrications with the sacred, that is, with Christianity, and the limits of the Catholic Christianization; religious syncretism between Christian faith and called beliefs pagan by the Church itself; and, within that scope, the representations of evil and ethics related to such perceptions as elements of medieval religiosity - present in the visigothic culture - which, despite extensive studies conducted until the present moment, require new approaches. Generally speaking, we propose to analyze the perception of evil and its representations in the long duration, the role and intentions of theologians and hagiographers, paying special attention to religiosity and its implications in the imaginary. As the main sources of our research, which are part of the Visigoth hagiographic corpus, are: Saint Emilian Life (Vita Sancti Aemiliani) of Braulio of Zaragoza; The Lives of the Saint Fathers of Merida (Vitas Sanctorum Patrum Emeretensium) and The Life of Saint Frutuoso (Vita Fructuosi) of unknown authors; The Life of St. Desiderius (Vita Desiderii), written by Sisebuto, and the autobiography of Valerius of Bierzo